EVALUASI PENYIMPANAN OBAT HIGH ALERT DI GUDANG DAN APOTEK RAWAT INAP DI INSTALASI FARMASI RUMAH SAKIT JIWA DAERAH PROVINSI JAMBI - Luthfiyyah, Annisa; Yudha Putra, Diky Okta; Sani K, Fathnur (Acta Pharmaceutica Indonesia, 2025)
The storage of high alert medications at the Regional Mental Hospital (RSJD) of Jambi Province is a crucial aspect of healthcare that impacts patient safety. This study aims to evaluate the compliance of high alert medication storage in the warehouse and inpatient pharmacy of RSJD Jambi Province based on the applicable Standard Operating Procedures (SOP). The research was based on observation with a qualitative descriptive approach, where data is collected through a checklist containing indicators of storage compliance. The results show that all storage procedures for high alert medications have been implemented effectively, with a compliance percentage of 100%. The medications are stored separately from other drugs, in accordance with FIFO and FEFO principles, and are clearly labeled. The conclusion of this study emphasizes that the management of high alert medications at RSJD Jambi Province has met the established standards, thereby minimizing the risk of errors in medication handling.